Self-other differences in the perceived authenticity of attitudes expressed toward social groups - Mata, André; Vaz, André (Frontiers in Psychology, 2024)
We assessed the perceived authenticity of attitudes expressed toward several social groups as a function of whether those attitudes were expressed by the self or by other people, and whether those expressions were automatic (without time to ponder) or controlled (without time constraints). Participants considered their controlled responses more authentic than their automatic responses. However, the same did not happen when considering others' attitudes.Implications for social perception are discussed.